Why the Monks took no Delight in the Buddha’s Words - Gombrich, Richard (Religions of South Asia, 2008)
Records of the Buddha’s sermons in the Pali Canon often end with a statement that the monks delighted in the Buddha’s words. However, the first sermon in one collection, the Majjhima Nikaya, says that they did not delight in them. though this reading is ancient, most modern editors have emended by removing the negative. this article argues that a careful study of the preceding text reveals why the negative is correct.